Ungulomycosis of cattle: etiological factors and pathogenetic mechanisms - Y. G. Krupnyk; S. V. Tsisinska; Yu. M. Lenjo (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2021)
Mycotic diseases, ie those caused by microscopic fungi, are widespread among animals. As for cattle, at present ungulomycosis has become the most widespread, in which keratolytic fungi affect the hooves of animals, causing complications such as deformities, pododermatitis, lesions of the hoof bone. Ungulomycosis (from the Latin ungula – hoof, Gr. Mykes – fungus) – a disease of the hooves, which are caused by microscopic fungi that have keratolytic properties. In most cases of ungulomycosis, its complications are most often registered, and not the disease itself, which does not allow to carry out effective preventive measures and treatment of animals in a timely manner. That is why the purpose of the work was to study and concretization the main factor of the disease and the contributing conditions for the disease. For this purpose the basic and additional clinical methods of research were used, including microscopy of the destroyed horn and sowing on nutrient media to determine the species content of microscopic fungi. The research was carried out in the farms of the western regions of Ukraine on cows of Black-Spotted and Holstein breeds in the stall period with tethered animals. It is found that the pathogenic action of microscopic fungi-keratomycetes on the hooves of cattle is carried out in the presence of favorable conditions of external and internal nature, primarily insufficient housing conditions and poor feeding. In particular, for osteodystrophy due to ungulomycosis, the destruction of the hoof's horn is accelerated, which complicates the pathological process. For purulent subdermatitis of traumatic origin, microscopic fungi-keratomycetes act as an additional or contributing factor to the disease. Further research will focus on the development of effective treatments and measures to prevent ungulomycosis.